Clinical Course, Myopathology and Challenge of Therapeutic Intervention in Pediatric Patients with Autoimmune-Mediated Necrotizing Myopathy - Adela Della Marina; Marc Pawlitzki; Tobias Ruck; Andreas van Baalen; Nadine Vogt; Bernd Schweiger; Swantje Hertel; Heike Kölbel; Heinz Wiendl; Corinna Preuße; Andreas Roos; Ulrike Schara-Schmidt (MDPI AG, 2021)
(1) Background: Immune-mediated necrotizing myopathy (IMNM) is a rare form of inflammatory muscle disease which is even more rare in pediatric patients. To increase the knowledge of juvenile IMNM, we here present the clinical findings on long-term follow-up, myopathological changes, and therapeutic strategies in two juvenile patients. (2) Methods: Investigations included phenotyping, determination of antibody status, microscopy on muscle biopsies, MRI, and response to therapeutic interventions. (3) Results: Anti-signal recognition particle (anti-SRP54) and anti- 3-hydroxy-3-methylglutarly coenzyme A reductase (anti-HMGCR) antibodies (Ab) were detected in the patients. Limb girdle presentation, very high CK-levels, and a lack of skin rash at disease-manifestation and an absence of prominent inflammatory signs accompanied by an abnormal distribution of α-dystroglycan in muscle biopsies initially hinted toward a genetically caused muscle dystrophy. Further immunostaining studies revealed an increase of proteins involved in chaperone-assisted autophagy (CASA), a finding already described in adult IMNM-patients. Asymmetrical muscular weakness was present in the anti-SRP54 positive Ab patient. After initial stabilization under therapy with intravenous immunoglobulins and methotrexate, both patients experienced a worsening of their symptoms and despite further therapy escalation, developed a permanent reduction of their muscle strength and muscular atrophy. (4) Conclusions: Diagnosis of juvenile IMNM might be complicated by asymmetric muscle weakness, lack of cutaneous features, absence of prominent inflammatory changes in the biopsy, and altered α-dystroglycan.